Analisis Pengaruh Penghargaan Finansial, Pelatihan Profesional Pengakuan Profesional, Nilai-Nilai Sosial Dan Lingkungan Kerja Terhadap Pemilihan Karir Akuntan Publik (Studi Empiris pada Mahasiswa PPAK di UNS, UGM dan STIE YKPN) - Kharismawati, Happy; , Dr. Noer Sasongko, SE, M.Si,Ak (2015)
The purpose of this research are to determine the effect of financial rewards, professional training, professional recognition, social values, and work environment on career selection of Public Accountant. Research samples are 79 Professional Accounting Education Students. Data analysis in this study are multiple linear regression analysis, goodness models test: The coefficient of determination (R2), F test and t test. The results showed that: (1) financial reward effecting on the career selection of Public Accountant, this is evidenced by the results of the t test to obtain the value of tcount > t table ( 2,360> 2,015) with a significance value of 0,023<0,05. (2) Professional training effecting on the career selection of Public Accountant, this is evidenced by the results of the t test to obtain the value of tcount > ttable (3,632> 2,015) with a significance value of 0,001<0,05. (3) Professional recognition has no effect on the career selection of Public Accountant, this is evidenced by the results of the t test to obtain the value of tcount < ttable (0,730 < 2,015) with a significance value of 0,469>0,05. (4) Social values has no effect on the career selection of Public Accountant, this is evidenced by the results of the t test to obtain the value of tcount < ttable (0,922 < 2,015) with a significance value of 0,361>0,05. (5) Work environment effecting on the career selection of Public Accountant, this is evidenced by the results of the t test to obtain the value of tcount > ttable (2,360> 2,015) with a significance value of 0,023<0,05.